2011
DOI: 10.1007/s11430-011-4219-9
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between hotspots and the Southwest Indian Ridge during the last 90 Ma: Implications on the formation of oceanic plateaus and intra-plate seamounts

Abstract: This study investigates the relationship between the hotspot-ridge interaction and the formation of oceanic plateaus and seamounts in the Southwest Indian Ocean. We first calculated the relative distance between the Southwest Indian Ridge (SWIR) and relevant hotspots on the basis of models of plate reconstruction, and then calculated the corresponding excess magmatic anomalies of the hotspots on the basis of residual bathymetry and Airy isostasy. The results reveal that the activities of the Marion hotspot can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
34
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 51 publications
(78 reference statements)
0
34
1
Order By: Relevance
“…Even assuming large temperature anomalies, however, it has been noted that the Hawaiian Swell, possibly the largest 9 thermal plume on the planet, has a peak amplitude of only ~1.4 km 43 while Ito et al 44 modeling the Iceland Swell found little over 1 km supported by mantle temperature variations of 180°C, with the rest being an isostatic response to crustal thickness. Thus, it is very unlikely that the geriatric Marion Plume could account for the 2.1-km depth anomaly along the Marion Rise.Mantle composition gradients along rises can explain their gravity signal, which when modeled assuming uniform mantle composition, predicts 8 to 10 km of crust on the Marion and Azores Rises 14,45 . Varying serpentinization depth is not a likely alternative as serpentine is unlikely to be stable to 9 or 10 km depth beneath a ridge.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Even assuming large temperature anomalies, however, it has been noted that the Hawaiian Swell, possibly the largest 9 thermal plume on the planet, has a peak amplitude of only ~1.4 km 43 while Ito et al 44 modeling the Iceland Swell found little over 1 km supported by mantle temperature variations of 180°C, with the rest being an isostatic response to crustal thickness. Thus, it is very unlikely that the geriatric Marion Plume could account for the 2.1-km depth anomaly along the Marion Rise.Mantle composition gradients along rises can explain their gravity signal, which when modeled assuming uniform mantle composition, predicts 8 to 10 km of crust on the Marion and Azores Rises 14,45 . Varying serpentinization depth is not a likely alternative as serpentine is unlikely to be stable to 9 or 10 km depth beneath a ridge.…”
mentioning
confidence: 99%
“…Notes: a) Marion -Zhang et al 14 ; b) Iceland& Azores -Wang et al 5 ; Galapagos -Canales et al 6 ; Marion -Zhang et al 14 . c) Maximum and minimum elevations are measured from shallowest point on axis, or midpoint of Iceland plateau to the rift valley axis point where average depth stabilizes or blocking transform.…”
mentioning
confidence: 99%
See 3 more Smart Citations